Association Between Prolonged Maternal Smokeless Tobacco Use & Preterm Birth In A Tertiary Level Hospital (The Planet, 2023)
Introduction: Preterm birth is more likely to happen when a mother has a health problem; such as smoking or using smokeless tobacco. 250 million women including 22% in the developed world and 9% in the developing world smoke tobacco on daily basis. In Bangladesh, more than 28% of women have been found to use smokeless tobacco frequently. The study intended to examine the association between prolonged smokeless tobacco (ST) use for more than 5 years by mothers and pregnancy outcomes including preterm birth. Methods and materials: Thisdescriptional retrospective cohort study was conducted at the Department of Paediatrics and Department of Gynecology and Obstetrics at Dhaka Medical College Hospital in Dhaka from January 2009 to December 2010. The study included a total of 300 mother-neonate pairs. Result: Most of the mothers in this study used shada, followed by jorda, shada+jorda, and gul. Preterm delivery was significantly associated with prolonged use of smokeless tobacco by mothers in the study group in comparison to the control group (P
Keywords: Smokeless; Tobacco; Preterm-birth